Fargo - Coen, Joel.; Houston, Gary.; Harve Presnell; Kristin Rudrüd; Peter Stormare; Steve Buscemi; Tony Denman; William H Macy (UK, USA Gramercy Pictures, 1996)
Jerry Lundegaard is in a financial jam and, out of desperation, comes up with a plan to hire someone to kidnap his wife and demand ransom from her wealthy father, to be secretly split between Jerry and the perpetrators. Jerry, who is not the most astute of individuals, hires a couple of real losers from the frozen northern reaches of Fargo, North Dakota for the job. Then things begin to slip from bad to worse as Jerry helplessly watches on.
Jerry Lundegaard's inept crime falls apart due to his and his henchmen's bungling and the persistent police work of pregnant Marge Gunderson.
Joel Coen
Languages : English, Turkish, Hungarian, Czech Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch
Keywords: Drama; Thriller; Crime